SAT0170 Ultrasound Composite Score for the Assessment of Inflammatory and Structural Pathologies in Psoriatic Arthritis. (10th June 2014) - Ficjan, A.; Husic, R.; Gretler, J.; Lackner, A.; Duftner, C.; Graninger, W.; Hermann, J.; Dejaco, C.
Abstract : Background: In clinical trials and routine practice of Psoriatic arthritis (PsA), disease activity is still monitored by RA specific clinical composites even if these measures are of questionable value for the assessment of PsA because of the heterogeneous nature of the disease affecting articular and extraarticular sites. (1) Objectives: To develop ultrasound composite score(s) for the assessment of joint, peri-articular and enthesal pathologies in Psoriatic Arthritis (PsA). Methods: Prospective study on 83 PsA patients with two study visits scheduled 6 months apart. B-mode and Power Doppler (PD-) findings were semiquantitatively scored at 68 joints (evaluating synovia, peritendinous tissue, tendons and bony changes) and 14 entheses. We used a hierarchical approach to construct a bilateral and a unilateral (focusing the dominant site) ultrasound composite scores. Discriminatory, internal and external validity, sensitivity, reliability and feasibility of the scores were tested. Results: The bilateral score includes wrists, 2nd, 3rd, 5th metacarpophalangeal (MCP) joints, 2nd, 3rd proximal (PIP) and distal (DIP) interphalangeal joints, knees, 1st metatarsophaangal (MTP) and 3rd DIP joints of feet (F-DIP), lateral epicondyles and distal patellar tendons. The unilateral score compromises wrist, 2nd, 5th MCPs, 1st, 2nd, 3rd PIPs, 2nd DIP, knee, 1st, 5th MTP, 1st F-PIP, 2nd, 3rd F-DIP, lateral epicondyle and distal patellar tendon of the dominant site. Both scores revealed a moderate to high sensitivity (bilateral composite 42-100%, unilateral 36-100%) to detect inflammatory and structural lesions. Data correlated with results from 68-joint/14-entheses score (corrcoeffs 0.39-1.0) and with clinical parameters (corrcoeffs 0-0.41). Patients achieving remission yielded greater reductions of ultrasound verified inflammation than patients did with stable clinical activity. Conclusions: We propose two new ultrasound composite scores for assessment of inflammatory and structural lesions in PsA. Both scores revealed discriminatory, internal and external validity, reliability and feasibility. References: Smolen JS, Braun J, Dougados M et al. Treating spondyloarthritis, including ankylosing spondylitis and psoriatic arthritis, to target: recommendations of an international task force. Ann Rheum Dis. 2014 Jan;73(1):6-16. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5188